Industry 4.0 and the current status as well as future prospects on logistics - Hofmann, Erik; Rüsch, Marco (Computers in industry, 2017)
•The paper seeks to answer questions regarding (i) the definition of Industry 4.0 and (ii) its impact on logistics management.•Industry 4.0 can be divided into: Cyber-physical systems, internet of things, internet of services and the smart factory.•An Industry 4.0 application model has been developed based on a detailed literature analysis.•Industry 4.0 is still at its very beginning and the future impact on logistics management are rather uncertain.•Nevertheless, the concept of Industry 4.0 seems to have enormous potentials – especially in the area of logistics management. Industry 4.0, referred to as the “Fourth Industrial Revolution”, also known as “smart manufacturing”, “industrial internet” or “integrated industry”, is currently a much-discussed topic that supposedly has the potential to affect entire industries by transforming the way goods are designed, manufactured, delivered and payed. This paper seeks to discuss the opportunities of Industry 4.0 in the context of logistics management, since implications are expected in this field. The authors pursue the goal of shedding light on the young and mostly undiscovered topic of Industry 4.0 in the context of logistics management, thus following a conceptual research approach. At first, a logistics-oriented Industry 4.0 application model as well as the core components of Industry 4.0 are presented. Different logistics scenarios illustrate potential implications in a practice-oriented manner and are discussed with industrial experts. The studies reveal opportunities in terms of decentralisation, self-regulation and efficiency. Moreover, it becomes apparent that the concept of Industry 4.0 still lacks a clear understanding and is not fully established in practice yet. The investigations demonstrate potential Industry 4.0 implications in the context of Just-in-Time/Just-in-Sequence and cross-company Kanban systems in a precise manner. Practitioners could use the described scenarios as a reference to foster their own Industry 4.0 initiatives, with respect to logistics management.